VIRTUAL LABORATORY BASED ON INGENHOUSZ EXPERIMENT MODELING: ENHANCING CONCEPTUAL UNDERSTANDING AND SCIENTIFIC LITERACY - Adnan Adnan; Syamsiah Syamsiah; Dian Aswita; Nur Hikmah; Nur Risnawati Kusuma; Sahla Sahira; Muh Yunus (Universitas Labuhanbatu, 2026)
Purpose – This study aims to evaluate the effectiveness of the Ingenhousz Experiment Virtual Laboratory, integrated with the GENIUS syntax, within a Blended Learning framework to accelerate students' conceptual understanding and science literacy in photosynthesis.Methodology – A quasi-experimental research with a Replicated Experimental Design was employed. The study involved 136 eleventh-grade science students at SMA Negeri 3 Makassar, divided into three experimental replication classes and one control class. Conceptual understanding was measured using a 20-item multiple-choice test, while science literacy was assessed through a 5-item essay test. Data were analyzed using descriptive statistics, N-Gain calculations, ANCOVA, and Least Significant Difference (LSD) post-hoc tests.Findings – Initial assessments indicated equivalent suboptimal cognitive baselines across all groups. Post-intervention, all replication classes demonstrated a profound cognitive escalation, achieving a